Beyond the Virtual Classroom: Computer Self-Efficacy and Its Effects on Learning Burnout in Asynchronous E-learning - Roihatul Millah; Romi Siswanto; Sitti Jamilah; Ardiana (JEELS (Journal of English Education and Linguistics Studies), 2025)
Many ELT students in asynchronous e-learning may experience burnout despite having adequate technological skills. Understanding how computer self-efficacy (CSE) relates to burnout is therefore essential to support their well-being. The study aimed to investigate the correlation between CSE and learning burnout and to examine whether CSE predicts burnout among ELT students in an Open and Distance Learning (ODL) university. Using a correlational–predictive design, data from 38 students were analyzed through Pearson correlation and simple linear regression. Results showed varied CSE levels: basic computer skills ranked highest, followed by media-related skills, while web-based skills were lowest. Students appeared more confident with basic functions than with online or media tools. Exhaustion emerged as the strongest burnout symptom. A significant positive correlation was found between CSE and learning burnout (r = 0.370, p = 0.022), and regression analysis showed that CSE significantly predicted burnout (F = 5.709, p = 0.022), accounting for 13.7% of the variance. Each unit increase in CSE corresponded to a 0.480-unit rise in burnout. These results challenge the assumption that higher technological competence always reduces burnout. Instead, students with stronger CSE may over-engage with digital tools, increasing exhaustion. The findings highlight the need for balanced technology use and thoughtful e-learning design to protect students’ well-being.